Capitalizing on the wealth of chemical data in the accretionary structures of aquatic taxa: Opportunities from across the tree of life - Zoë A. Doubleday; Louise Hosking; Jasper Willoughby; Minoli Dias; Natasha Leclerc; Shanie Brault Nikolajew; Melita Peharda; Arieli Tristão Rézio; Clive Trueman (Limnology and Oceanography Letters)
Abstract Aquatic organisms are natural data loggers and record chemical variations within hardened accretionary structures like shells and teeth. Chemical sclerochronology is the study of these chemical variations through time and how they are used to understand environmental change and the physiology and ecology of species. While sclerochronology research has largely focused on bivalves, teleost fish, and hard corals, there are many other aquatic taxa rich with time‐resolved chemical data. To expand focus to these “other” taxa and determine the state‐of‐play, we compiled a database of chemical sclerochronology studies spanning nine living phyla and 19 classes. We then examined research trends and knowledge gaps across these taxa and showcase their exciting potential to collect critical data and address pressing environmental and ecological challenges. We hope this synthesis will encourage further research on species across the tree of life, as well as foster collaboration among the established and lesser‐known fields of sclerochronology.